Enhanced constrained application protocol for secured medical data transmission model for internet of things. (26th April 2020) - Gobichettipalayam Krishnasamy, Kamalam; Selvaraj, Anandamurugan
Abstract: The medical data produced from various sensors of sensitive information so there is a need to secure them through security solutions. At present, many security solutions are available in the market to secure the medical data. Transport layer security (TLS) is designed to transfer the client from the client to the server in a more secure manner. The major advantage of using TLS is it will not lose any data while transferring the message from client to server. Datagram transport layer security (DTLS) is designed specifically to use in constrained networks. The DTLS protocol consists of major components like base protocol, record layer, and handshake protocol. The main disadvantage of DTLS is the attacker can send multiple Hello messages to the server. This can cause an attack against the server and this attack encourages a new connection between the client and server and also it increases required bandwidth and resources for every message. The main objective of the proposed work is to use the constrained application protocol (CoAP) with DTLS in place of user datagram protocol (UDP) for the secure transmission of data. To evaluate the efficiency of the system, the packet loss ratio, data transmission time, and handshake time are calculated.